Improvement in nutritional quality of traditional unleavened flat bread using Quality Protein Maize - Kaur, Navjot; Kumar, Ramesh; Singh, Alla; Shobha, D.; Das, Abhijit Kumar; Chaudhary, Dharampaul; Kaur, Yashmeet; Kumar, Pardeep; Sharma, Priti; Singh, Baljit (Frontiers in Nutrition, 2022)
Maize grains are consumed majorly in the form of unleavened flat bread (chapatti) in South East Asian region. The landraces are better accepted for their chapatti making attributes like grain colour and good organoleptic properties. However, these cultivars are low in essential amino acids, particularly lysine and tryptophan content. Hence, an investigation was performed to identify maize genotypes with high nutritional value coupled with good chapatti making qualities. Seven genotypes, comprising two QPM hybrids, two normal maize hybrids and three normal white maize landraces were assessed for their physical characteristics, proximate composition and chapatti making quality. Landrace 593 showed highest protein and ash content. Flours obtained from different genotypes were significantly different (p ≤0.001) in terms of protein content, color value, textural as well as mineral content. PMH 10 and IQMH 203 exhibited highest and lowest hydration index, respectively. Two QPM hybrids showed significantly higher lysine and tryptophan content as compared to other genotypes. QPM hybrids were identified as the promising material with improved nutritional quality with respect to chapatti making. In combination with mustard greens, maize chapatti constitutes an important traditional delicacy in north India. The enhanced nutritional quality of QPM chapattis is an added advantage. We show differentiation of chapattis made from QPM and normal maize using a rapid protocol developed previously. This is expected to enable development and quality control of commercial enterprises based on high protein quality QPM.